2004
DOI: 10.1007/s10529-004-4579-8
|View full text |Cite
|
Sign up to set email alerts
|

Recent developments on cellulases and carbohydrate-binding modules with cellulose affinity

Abstract: This review concerns basic research on cellulases and cellulose-specific carbohydrate-binding modules (CBMs). As a background, glycosyl hydrolases are also briefly reviewed. The nomenclature of cellulases and CBMs is discussed. The main cellulase-producing organisms and their cellulases are described. Synergy, enantioseparation, cellulases in plants, cellulosomes, cellulases and CBMs as analytical tools and cellulase-like enzymes are also briefly reviewed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0
4

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(42 citation statements)
references
References 101 publications
0
38
0
4
Order By: Relevance
“…To hydrolyze cellulose, endoglucanases locate surface sites randomly along the cellodextrin and insert a water molecule in the intramolecular -1,4-glucosidic bonds, creating a new reducing and non-reducing chain end pair; exoglucanases processively cleave cellulose chains at the ends to release cellobiose, and -glucosidases convert cellobiose to glucose and thus relieve the system from end-product inhibition [12]. However, the division into endo-and exoglucanases in many cases is not absolute and may have the risk of over-simpliWcation [2,10,11,14,29,30]. A processive endoglucanase in ThermobiWda fusca E4 has been documented [14], and it has been suggested that exoglucanases could exhibit some endoglucanase activity due to temporary conformational structural changes [33,38].…”
Section: Introductionmentioning
confidence: 99%
“…To hydrolyze cellulose, endoglucanases locate surface sites randomly along the cellodextrin and insert a water molecule in the intramolecular -1,4-glucosidic bonds, creating a new reducing and non-reducing chain end pair; exoglucanases processively cleave cellulose chains at the ends to release cellobiose, and -glucosidases convert cellobiose to glucose and thus relieve the system from end-product inhibition [12]. However, the division into endo-and exoglucanases in many cases is not absolute and may have the risk of over-simpliWcation [2,10,11,14,29,30]. A processive endoglucanase in ThermobiWda fusca E4 has been documented [14], and it has been suggested that exoglucanases could exhibit some endoglucanase activity due to temporary conformational structural changes [33,38].…”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms and the effects of cellulase on cellulose fibers have been extensively reviewed. [9][10][11][12] Cellulase is a general term for a group of enzymes that hydrolyze the b-(1,4)-linkages in cellulose. Cellulase consists of three different enzymes that act synergistically in the hydrolysis of cellulose.…”
Section: Introductionmentioning
confidence: 99%
“…However, the enzymatic hydrolysis reaction (most commonly with cellulases from the fungus Trichoderma reesei) is (still) too expensive (2.5-5 US cent per liter (10-20 US cents per gallon) of ethanol produced) and time-consuming (about 100-fold slower than the average fermentation rate with yeast) (Schubert, 2006;Gray et al, 2006). Many new enzymes from bacteria and fungi have been isolated and characterized in the last few years (Hildén & Johansson, 2004). Recently, the metagenome of the hindgut of the wood-feeding termite Nasutitermes has been analyzed with the aim to find novel cellulases (Warnecke et al, 2007).…”
Section: Cellulosic Biofuelsmentioning
confidence: 99%